Importance of Michaelis Constants for Cancer Cell Redox Balance and Lactate Secretion - Revisiting the Warburg Effect - Niepmann, Michael; Justus Liebig University Giessen (My University, 2024)
Cancer cells metabolize a large fraction of glucose to lactate, even under a sufficient oxygen supply. This phenomenon—the “Warburg Effect”—is often regarded as not yet understood. Cancer cells change gene expression to increase the uptake and utilization of glucose for biosynthesis pathways and glycolysis, but they do not adequately up-regulate the tricarboxylic acid (TCA) cycle and oxidative phosphorylation (OXPHOS). Thereby, an increased glycolytic flux causes an increased production of cytosolic NADH. However, since the corresponding gene expression changes are not neatly fine-tuned in the cancer cells, cytosolic NAD+ must often be regenerated by loading excess electrons onto pyruvate and secreting the resulting lactate, even under sufficient oxygen supply. Interestingly, the Michaelis constants (KM values) of the enzymes at the pyruvate junction are sufficient to explain the priorities for pyruvate utilization in cancer cells: 1. mitochondrial OXPHOS for efficient ATP production, 2. electrons that exceed OXPHOS capacity need to be disposed of and secreted as lactate, and 3. biosynthesis reactions for cancer cell growth. In other words, a number of cytosolic electrons need to take the “emergency exit” from the cell by lactate secretion to maintain the cytosolic redox balance.
Keywords: ddc:570